EXPLORING THE NEUROENDOCRINE CONTROL OF REPRODUCTION IN VERTEBRATES: FROM GONADOTROPIN-RELEASING HORMONE TO FERTILITY - Taghreed Ghali Najim; Ameer Ahmed Ali; Rawaa saad awadh; Elaf hussein skhail (Journal of Medical Genetics and Clinical Biology, 2024)
The aims of this study are to review the neuroendocrine control of reproduction in vertebrates with specific emphasis on Gonadotropin-Releasing Hormone (GnRH) expression, hormone secretion, gene up regulation, and reproduction behavior in different vertebrates which includes chickens and rats. There was a highly statistically significant rise in Luteinizing Hormone (LH) and Follicle-Stimulating Hormone (FSH) levels in the: GnRH prompted gonadotropin release – The results from this study confirm the releasing hormone’s action in stimulating the gonadotropic hormones. These results showed that there were significant improvements in the reproductive function related genes, and the pathway analysis was conducted, which presented the activation of the GnRH signaling, MAPK signaling, and ovarian steroidogenesis etc. IHC and IF experiments corroborated those findings and revealed increased levels of LH, FSH, and GnRH receptors. As for behavioral interactions of the three species, all of them exhibited eventual copulatory behaviors following GnRH treatment. These results are in concordance with previous reports published in the literature and corroborate the fact that GnRH is evolutionarily conserved in all the classes of vertebrates and thus, it may have therapeutic applications in the management of reproductive diseases in humans. Thus, the findings obtained contribute to the creation of a stably developing foundation for further investigation of the neuroendocrine regulation of reproduction and the development of approaches to address reproductive health issues